Anti-UV epoxy resin copper-clad plate and manufacturing method thereof
By using modified aluminum-titanium composite oxides as fillers, the UV resistance, heat resistance and mechanical properties of epoxy resin copper clad are improved, and the problem of poor performance of traditional copper clad plates in these aspects is solved, meeting the demand for high-performance copper clad plates in electronic products.
Patent Information
- Application Number
- CN202411682327.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Traditional epoxy resin-based copper clad plates do not perform well in terms of heat resistance and UV resistance, and it is difficult to meet the high-performance needs brought about by the renewal of electronic products.
A resin glue solution composed of bisphenol A type epoxy resin, flame retardant, curing agent, accelerator, filler and solvent is used to prepare an aluminum-titanium composite oxide with a aluminum oxide-covered titanium dioxide structure as a filler through hydrothermal reaction and calcination to improve the dispersion of titanium dioxide and inhibit its photocatalytic degradation activity.
It significantly improves the UV resistance, heat resistance and mechanical properties of epoxy resin copper clad plate, and meets the high requirements for copper clad plate performance of high-density and high-multilayer electronic products.
Smart Images

Figure BDA0005148659550000061 
Figure BDA0005148659550000071 
Figure BDA0005148659550000072
Abstract
Description
Technical Field
[0001] The invention relates to a copper-clad laminate, in particular to an anti-UV epoxy resin copper-clad laminate and a manufacturing method thereof. Background Art
[0002] With the demand for electronic products to be light, thin, short, small and digital, miniaturization, multi-function, high performance and high reliability have become the mainstream development direction, making PCBs move towards high density and high multi-layer. The requirements for line width, line spacing, aperture, hole wall and other processes in the production of PCB industry are also gradually moving towards high integration, high density and high multi-layer. With the development of high-density installation technology, especially the full implementation of lead-free and the rapid development of surface mounting technology, the requirements for the performance of copper clad laminates are getting higher and higher.
[0003] Copper clad laminate is a composite material that is made of resin and reinforcing materials, and is hot-pressed and covered with copper foil on one or both sides. Copper clad laminates mainly include glass fiber cloth-based copper clad laminates, non-woven fabric-based copper clad laminates, composite-based copper clad laminates, and synthetic fiber cloth-based copper clad laminates. Epoxy resin is widely used in copper clad laminates. Epoxy resin has the characteristics of small curing shrinkage, high viscosity of cured products, and good chemical corrosion resistance. However, with the upgrading of electronic products, the performance of traditional epoxy resin-based copper clad laminates in terms of heat resistance and UV resistance is not ideal. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a UV-resistant epoxy resin copper-clad laminate, which has good UV resistance, heat resistance and mechanical properties.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A UV-resistant epoxy resin copper-clad laminate. The resin glue used in manufacturing the UV-resistant epoxy resin copper-clad laminate is made of the following components in parts by weight: 45-55 parts of bisphenol A epoxy resin, 18-22 parts of flame retardant, 7-10 parts of curing agent, 0.1-0.2 parts of accelerator, 45-48 parts of filler and 60-65 parts of solvent.
[0007] Furthermore, the bisphenol A epoxy resin of the present invention is epoxy resin E-44.
[0008] Furthermore, the flame retardant of the present invention is toluene diphenyl phosphate.
[0009] Furthermore, the curing agent of the present invention is 4,4'-diaminodiphenylmethane.
[0010] Furthermore, the promoter of the present invention is 2-ethyl-4-methylimidazole.
[0011] Furthermore, the filler of the present invention is prepared by the following steps:
[0012] A1. Aluminum nitrate was added to deionized water and mixed to obtain an aluminum nitrate solution. Titanium dioxide was added to an ethanol aqueous solution and ultrasonically stirred for 30 minutes to obtain a titanium dioxide suspension. The aluminum nitrate solution and ammonia water were added to the titanium dioxide suspension, and the pH value was adjusted to 10. The mixture was heated to 110°C and kept warm for 4 hours to obtain a reaction solution. The reaction solution was centrifuged to obtain a solid. The solid was washed three times with anhydrous ethanol and deionized water, respectively, and dried and calcined in a muffle furnace at 500°C for 3 hours to obtain an aluminum-titanium composite oxide.
[0013] A2. Add vinyl triethoxysilane to anhydrous ethanol, adjust the pH value to 5, and stir until the mixture is uniform to obtain a silane solution, add the aluminum-titanium composite oxide obtained in step A1 to the silane solution, heat to 65°C, and stir to react for 7 hours to obtain a reaction solution 2, centrifuge the reaction solution 2 to obtain a solid 2, wash the solid 2 with anhydrous ethanol and deionized water for 3 times, respectively, and dry to obtain a pretreated aluminum-titanium composite oxide;
[0014] A3. Add the pretreated aluminum-titanium composite oxide, styrene, PVP, and AIBN obtained in step A2 to an ethanol-water solution, heat to 85°C after passing nitrogen, and stir to react for 9 hours to obtain reaction solution three. Centrifuge the reaction solution three to obtain solid material three. Wash the solid material three with anhydrous ethanol and deionized water for three times respectively, and dry it to obtain a filler.
[0015] Further, in step A1 of the present invention, the titanium dioxide is rutile titanium dioxide, the concentration of the aluminum nitrate solution is 0.2 g / mL, the volume concentration of the ethanol aqueous solution is 50%, the ratio of titanium dioxide to the ethanol aqueous solution is 0.1 g:1 mL, the concentration of ammonia water is 0.25 g / mL, the volume ratio of the aluminum nitrate solution, ammonia water, and the titanium dioxide suspension is 1:0.2:1, the centrifugal speed is 5000 rpm, the centrifugal time is 10 minutes, the drying temperature is 75°C, and the drying time is 8 hours;
[0016] In step A2, the weight ratio of vinyltriethoxysilane, anhydrous ethanol, and the aluminum-titanium composite oxide obtained in step A1 is 1:50:40, the centrifugal speed is 5000 rpm, the centrifugal time is 10 minutes, the drying temperature is 75° C., and the drying time is 8 hours;
[0017] In step A3, the volume concentration of the ethanol aqueous solution is 50%, the weight ratio of the pretreated aluminum-titanium composite oxide, styrene, PVP, AIBN, and the ethanol aqueous solution obtained in step A2 is 50:2.5:50:100:1000, the centrifugal speed is 5000 rpm, the centrifugal time is 10 minutes, the drying temperature is 75°C, and the drying time is 8 hours.
[0018] Furthermore, the solvent of the present invention is composed of butanone and propylene glycol methyl ether in equal weights.
[0019] Another technical problem to be solved by the present invention is to provide a method for manufacturing the above-mentioned UV-resistant epoxy resin copper-clad laminate.
[0020] To solve the above technical problems, the technical solution is:
[0021] A method for manufacturing a UV-resistant epoxy resin copper-clad laminate comprises the following steps:
[0022] B1. Weigh the components of the resin glue in parts by weight, mix the bisphenol A epoxy resin, flame retardant, curing agent, accelerator, filler, solvent, and stir to obtain a resin glue;
[0023] B2. The glass fiber cloth is impregnated with the resin solution obtained in step B1 and baked for 5-10 minutes to obtain a prepreg;
[0024] B3. Stack 8 prepregs obtained in step B2 together to obtain a multilayer prepreg, cover the upper and lower surfaces of the multilayer prepreg with a copper foil respectively, place them in a hot press, and cool to room temperature to obtain a UV-resistant epoxy resin copper-clad laminate.
[0025] Furthermore, in step B2 of the present invention, the baking temperature is 150-180° C.; the hot pressing temperature is 200-230° C., the pressure is 5-8 MPa, and the time is 1-3 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] Titanium dioxide has excellent ultraviolet absorption and shielding capabilities, so its UV resistance is good, but its dispersibility in epoxy resin is poor, and titanium dioxide also has strong photocatalytic properties, which will degrade part of the epoxy resin, resulting in a decrease in mechanical properties. Therefore, the present invention firstly prepares aluminum titanium composite oxide having an aluminum oxide-coated titanium dioxide structure by hydrothermal reaction, roasting, etc. of aluminum nitrate, titanium dioxide, ammonia water, etc., and aluminum oxide can play a good barrier role and inhibit the photocatalytic degradation activity of titanium dioxide. Then, vinyl triethoxysilane is used to react with the hydroxyl groups on the surface of the aluminum titanium composite oxide, and double bonds are introduced. The pretreated aluminum-titanium composite oxide is prepared by a functional group, and then the pretreated aluminum-titanium composite oxide is cross-linked and polymerized with styrene through PVP and AIBN through the double bond functional groups on the surface to obtain a filler with styrene as a coating layer. The styrene coating layer in the filler can effectively improve the dispersibility of titanium dioxide in epoxy resin, thereby effectively improving the UV resistance of the resin glue and the epoxy resin copper clad laminate, and will not lose the mechanical properties of the resin glue and the epoxy resin copper clad laminate; in addition, the aluminum oxide in the filler prepared by the present invention has excellent high temperature resistance, so it can also effectively improve the heat resistance of the resin glue and the epoxy resin copper clad laminate. DETAILED DESCRIPTION
[0028] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention but are not intended to limit the present invention.
[0029] Example 1
[0030] The invention discloses an anti-UV epoxy resin copper-clad laminate. The resin glue used in manufacturing the epoxy resin copper-clad laminate is prepared from the following components in parts by weight: 50 parts of epoxy resin E-44, 20 parts of toluene diphenyl phosphate, 8 parts of 4,4'-diaminodiphenylmethane, 0.1 part of 2-ethyl-4-methylimidazole, 46 parts of filler, and 63 parts of a solvent composed of butanone and propylene glycol methyl ether in equal weights.
[0031] The filling is made by the following steps:
[0032] A1. Aluminum nitrate was added to deionized water and mixed to obtain an aluminum nitrate solution having a concentration of 0.2 g / mL. Rutile titanium dioxide was added to an ethanol aqueous solution having a volume concentration of 50% in a ratio of 0.1 g: 1 mL and ultrasonically stirred for 30 minutes to obtain a titanium dioxide suspension. Aluminum nitrate solution and ammonia water at a concentration of 0.25 g / mL were added to the titanium dioxide suspension. The volume ratio of aluminum nitrate solution, ammonia water and titanium dioxide suspension was 1:0.2:1. The pH value was adjusted to 10, heated to 110 ° C and kept warm for 4 hours to obtain a reaction solution. The reaction solution was centrifuged at 5000 rpm for 10 minutes to obtain a solid. The solid was washed three times with anhydrous ethanol and deionized water, respectively, and dried at 75 ° C for 8 hours and then placed in a muffle furnace at 500 ° C for 3 hours to obtain an aluminum-titanium composite oxide.
[0033] A2. Add vinyl triethoxysilane to anhydrous ethanol, adjust the pH value to 5 and stir until the mixture is uniform to obtain a silane solution, add the aluminum-titanium composite oxide obtained in step A1 to the silane solution, the weight ratio of vinyl triethoxysilane, anhydrous ethanol and the aluminum-titanium composite oxide obtained in step A1 is 1:50:40, heat to 65°C and stir to react for 7 hours to obtain a reaction solution 2, centrifuge the reaction solution 2 at 5000 rpm for 10 minutes to obtain a solid 2, wash the solid 2 with anhydrous ethanol and deionized water for 3 times respectively, and dry at 75°C for 8 hours to obtain a pretreated aluminum-titanium composite oxide;
[0034] A3. The pretreated aluminum-titanium composite oxide, styrene, PVP, and AIBN obtained in step A2 are added to an ethanol aqueous solution with a volume concentration of 50%, wherein the weight ratio of the pretreated aluminum-titanium composite oxide, styrene, PVP, AIBN, and the ethanol aqueous solution obtained in step A2 is 50:2.5:50:100:1000. After passing nitrogen, the mixture is heated to 85°C, stirred and reacted for 9 hours to obtain a reaction solution three. The reaction solution three is centrifuged at 5000 rpm for 10 minutes to obtain a solid substance three. The solid substance three is washed three times with anhydrous ethanol and deionized water respectively, and dried at 75°C for 8 hours to obtain a filler.
[0035] The manufacturing method of this embodiment includes the following steps:
[0036] B1. Weigh the components of the resin glue in parts by weight, epoxy resin E-44, toluene diphenyl phosphate, 4,4'-diaminodiphenylmethane, 2-ethyl-4-methylimidazole, filler, a solvent composed of equal weights of butanone and propylene glycol methyl ether, and stir to obtain a resin glue;
[0037] B2. The glass fiber cloth was impregnated with the resin solution obtained in step B1 and baked at 170°C for 7 minutes to obtain a prepreg;
[0038] B3. Stack 8 prepregs obtained in step B2 together to obtain a multilayer prepreg, cover the upper and lower surfaces of the multilayer prepreg with a copper foil respectively, place them in a hot press for hot pressing, and after cooling to room temperature, obtain a UV-resistant epoxy resin copper-clad laminate. The hot pressing temperature is 220°C, the pressure is 6 MPa, and the time is 2 hours.
[0039] Example 2
[0040] The invention discloses an anti-UV epoxy resin copper-clad laminate. The resin glue used in manufacturing the epoxy resin copper-clad laminate is prepared from the following components in parts by weight: 4445 parts of epoxy resin E-4, 18 parts of toluene diphenyl phosphate, 7 parts of 4,4'-diaminodiphenylmethane, 0.1 part of 2-ethyl-4-methylimidazole, 45 parts of filler, and 60 parts of a solvent composed of butanone and propylene glycol methyl ether in equal weights.
[0041] The preparation steps of the filler are the same as those in Example 1.
[0042] The manufacturing method of this embodiment includes the following steps:
[0043] B1. Weigh the components of the resin glue in parts by weight, epoxy resin E-44, toluene diphenyl phosphate, 4,4'-diaminodiphenylmethane, 2-ethyl-4-methylimidazole, filler, a solvent composed of equal weights of butanone and propylene glycol methyl ether, and stir to obtain a resin glue;
[0044] B2. The glass fiber cloth was impregnated with the resin solution obtained in step B1 and baked at 150°C for 10 minutes to obtain a prepreg;
[0045] B3. Stack 8 prepregs obtained in step B2 together to obtain a multilayer prepreg, cover the upper and lower surfaces of the multilayer prepreg with a copper foil respectively, place them in a hot press for hot pressing, and after cooling to room temperature, obtain a UV-resistant epoxy resin copper-clad laminate. The hot pressing temperature is 200°C, the pressure is 8 MPa, and the time is 3 hours.
[0046] Example 3
[0047] The invention discloses an anti-UV epoxy resin copper-clad laminate. The resin glue used in manufacturing the epoxy resin copper-clad laminate is prepared from the following components in parts by weight: 55 parts of epoxy resin E-44, 22 parts of toluene diphenyl phosphate, 10 parts of 4,4'-diaminodiphenylmethane, 0.2 parts of 2-ethyl-4-methylimidazole, 48 parts of filler, and 65 parts of a solvent composed of butanone and propylene glycol methyl ether in equal weights.
[0048] The preparation steps of the filler are the same as those in Example 1.
[0049] The manufacturing method of this embodiment includes the following steps:
[0050] B1. Weigh the components of the resin glue in parts by weight, epoxy resin E-44, toluene diphenyl phosphate, 4,4'-diaminodiphenylmethane, 2-ethyl-4-methylimidazole, filler, a solvent composed of equal weights of butanone and propylene glycol methyl ether, and stir to obtain a resin glue;
[0051] B2. The glass fiber cloth was impregnated with the resin solution obtained in step B1 and baked at 180°C for 5 minutes to obtain a prepreg;
[0052] B3. Stack 8 prepregs obtained in step B2 together to obtain a multilayer prepreg, cover the upper and lower surfaces of the multilayer prepreg with a copper foil respectively, place them in a hot press for hot pressing, and after cooling to room temperature, obtain a UV-resistant epoxy resin copper-clad laminate. The hot pressing temperature is 230°C, the pressure is 5 MPa, and the time is 1 hour.
[0053] Example 4
[0054] The invention discloses an anti-UV epoxy resin copper-clad laminate. The resin glue used in manufacturing the epoxy resin copper-clad laminate is prepared from the following components in parts by weight: 1 part of epoxy resin E-445, 21 parts of toluene diphenyl phosphate, 9 parts of 4,4'-diaminodiphenylmethane, 0.2 part of 2-ethyl-4-methylimidazole, 47 parts of filler, and 64 parts of a solvent composed of butanone and propylene glycol methyl ether in equal weights.
[0055] The preparation steps of the filler are the same as those in Example 1.
[0056] The manufacturing method of this embodiment includes the following steps:
[0057] B1. Weigh the components of the resin glue in parts by weight, epoxy resin E-44, toluene diphenyl phosphate, 4,4'-diaminodiphenylmethane, 2-ethyl-4-methylimidazole, filler, a solvent composed of equal weights of butanone and propylene glycol methyl ether, and stir to obtain a resin glue;
[0058] B2. The glass fiber cloth was impregnated with the resin solution obtained in step B1 and baked at 160°C for 9 minutes to obtain a prepreg;
[0059] B3. Stack 8 prepregs obtained in step B2 together to obtain a multilayer prepreg, cover the upper and lower surfaces of the multilayer prepreg with a copper foil respectively, place them in a hot press for hot pressing, and after cooling to room temperature, obtain a UV-resistant epoxy resin copper-clad laminate. The hot pressing temperature is 210°C, the pressure is 7 MPa, and the time is 2.5 hours.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the resin glue component does not include fillers, and the preparation step of the fillers is omitted.
[0062] Comparative Example 2
[0063] The difference from Example 1 is that the preparation step of the filler in the resin glue component does not include A3, that is, the filler is a pretreated aluminum-titanium composite oxide that does not contain a styrene coating layer.
[0064] Comparative Example 3
[0065] The difference from Example 1 is that the preparation step of the filler in the resin glue component does not include A1, the aluminum-titanium composite oxide used in step A2 is replaced by rutile titanium dioxide, the pretreated titanium dioxide prepared in step A2, the pretreated aluminum-titanium composite oxide used in step A3 is replaced by pretreated titanium dioxide, and the prepared filler does not contain aluminum oxide.
[0066] Experimental Example 1: Mechanical Properties
[0067] Test reference standard / method: IPC-TM-6502.4.4.
[0068] Test object and target: Bending strength of epoxy resin copper clad laminates prepared in Examples 1-4, Comparative Example 2 and Comparative Example 3 at room temperature.
[0069] The higher the bending strength, the better the mechanical properties. The test results are shown in Table 1:
[0070]
[0071] Table 1
[0072] As can be seen from Table 1, the bending strengths of Examples 1-4 of the present invention are all relatively high, indicating that the present invention has good mechanical properties. Some components and preparation steps used in Comparative Examples 2 and 3 are different from those in Example 1. Compared with Example 1, the bending strength of Comparative Example 2 is reduced, indicating that compared with the pretreated aluminum-titanium composite oxide not containing a styrene coating layer, the filler prepared by the present invention has better dispersibility and better effect on improving the mechanical properties of the epoxy resin copper clad laminate; compared with Example 1, the bending strength of Comparative Example 3 is also reduced, indicating that the aluminum oxide in the filler prepared by the present invention can effectively inhibit the photocatalytic degradation activity of titanium dioxide.
[0073] Experimental Example 2: UV resistance test
[0074] Test method: GB / T 14522-2008.
[0075] Test instrument: LUV ultraviolet accelerated aging test chamber.
[0076] Test object, target: bending strength retention rate of epoxy resin copper clad laminates prepared in Examples 1-4, Comparative Example 1, and Comparative Example 2, bending strength retention rate = bending strength after UV aging / original bending strength × 100%, irradiation light source is UVA-340 fluorescent ultraviolet lamp (0.76W / m 2 ), UV aging time is 300 hours.
[0077] The higher the bending strength retention rate, the better the UV resistance. The test results are shown in Table 2:
[0078]
[0079] Table 2
[0080] As can be seen from Table 2, the bending strength retention rates of Examples 1-4 of the present invention are all high, indicating that the present invention has good anti-UV performance. Some components and preparation steps used in Comparative Examples 1 and 2 are different from those in Example 1. Compared with Example 1, the bending strength retention rate of Comparative Example 1 is much lower than that of Example 1, indicating that the filler prepared by the present invention can greatly improve the anti-UV performance of the epoxy resin copper clad laminate; the bending strength retention rate of Comparative Example 2 is also reduced, indicating that compared with the pretreated aluminum-titanium composite oxide not containing a styrene coating layer, the filler prepared by the present invention has better dispersibility and better effect on improving the anti-UV performance of the epoxy resin copper clad laminate.
[0081] Experimental Example 3: Heat resistance test
[0082] Test reference standard / method: IPC-TM-6502.4.24.6, TGA method.
[0083] Test instrument: comprehensive thermal analyzer.
[0084] Test object and target: the temperature at which the epoxy resin copper clad laminates prepared in Examples 1-4 and Comparative Example 3 lose 5% of their weight.
[0085] The higher the temperature when the weight loss is 5%, the better the heat resistance. The test results are shown in Table 3:
[0086]
[0087]
[0088] Table 3
[0089] As can be seen from Table 3, the temperatures at which the weight loss of 5% in Examples 1-4 of the present invention is high, indicating that the present invention has good heat resistance. Some components and preparation steps used in Comparative Example 3 are different from those in Example 1. Compared with Example 1, the temperature at which the weight loss of 5% in Comparative Example 3 is lower, indicating that the aluminum oxide in the filler prepared by the present invention can effectively improve the heat resistance of the epoxy resin copper clad laminate.
[0090] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A UV-resistant epoxy copper-clad laminate, characterized in that: The resin glue used in manufacturing the UV-resistant epoxy resin copper-clad laminate is made of the following components in parts by weight: 45-55 parts of bisphenol A epoxy resin, 18-22 parts of flame retardant, 7-10 parts of curing agent, 0.1-0.2 parts of accelerator, 45-48 parts of filler and 60-65 parts of solvent.
2. The UV-resistant epoxy copper-clad laminate according to claim 1, characterized in that: The bisphenol A type epoxy resin is epoxy resin E-44.
3. The UV-resistant epoxy copper-clad laminate according to claim 1, characterized in that: The flame retardant is toluene diphenyl phosphate.
4. The UV-resistant epoxy copper-clad laminate according to claim 1, characterized in that: The curing agent is 4,4'-diaminodiphenylmethane.
5. The UV-resistant epoxy copper-clad laminate according to claim 1, characterized in that: The accelerator is 2-ethyl-4-methylimidazole.
6. The UV-resistant epoxy copper-clad laminate according to claim 1, characterized in that: The filler is prepared by the following steps: A1. Aluminum nitrate was added to deionized water and mixed to obtain an aluminum nitrate solution. Titanium dioxide was added to an ethanol aqueous solution and ultrasonically stirred for 30 minutes to obtain a titanium dioxide suspension. The aluminum nitrate solution and ammonia water were added to the titanium dioxide suspension, and the pH value was adjusted to 10. The mixture was heated to 110°C and kept warm for 4 hours to obtain a reaction solution. The reaction solution was centrifuged to obtain a solid. The solid was washed three times with anhydrous ethanol and deionized water, respectively, and dried and calcined in a muffle furnace at 500°C for 3 hours to obtain an aluminum-titanium composite oxide. A2. Add vinyl triethoxysilane to anhydrous ethanol, adjust the pH value to 5, and stir until the mixture is uniform to obtain a silane solution, add the aluminum-titanium composite oxide obtained in step A1 to the silane solution, heat to 65°C, and stir to react for 7 hours to obtain a reaction solution 2, centrifuge the reaction solution 2 to obtain a solid 2, wash the solid 2 with anhydrous ethanol and deionized water for 3 times, respectively, and dry to obtain a pretreated aluminum-titanium composite oxide; A3. Add the pretreated aluminum-titanium composite oxide, styrene, PVP, and AIBN obtained in step A2 to an ethanol-water solution, heat to 85°C after passing nitrogen, and stir to react for 9 hours to obtain reaction solution three. Centrifuge the reaction solution three to obtain solid material three. Wash the solid material three with anhydrous ethanol and deionized water for three times respectively, and dry it to obtain a filler.
7. The UV-resistant epoxy copper-clad laminate according to claim 6, characterized in that: In the step A1, the concentration of the aluminum nitrate solution is 0.2 g / mL, the volume concentration of the ethanol aqueous solution is 50%, the ratio of titanium dioxide to the ethanol aqueous solution is 0.1 g:1 mL, the concentration of ammonia water is 0.25 g / mL, the volume ratio of the aluminum nitrate solution, ammonia water, and titanium dioxide suspension is 1:0.2:1, the centrifugal speed is 5000 rpm, the centrifugal time is 10 minutes, the drying temperature is 75°C, and the drying time is 8 hours; In step A2, the weight ratio of vinyltriethoxysilane, anhydrous ethanol, and the aluminum-titanium composite oxide obtained in step A1 is 1:50:40, the centrifugal speed is 5000 rpm, the centrifugal time is 10 minutes, the drying temperature is 75° C., and the drying time is 8 hours; In step A3, the volume concentration of the ethanol aqueous solution is 50%, the weight ratio of the pretreated aluminum-titanium composite oxide, styrene, PVP, AIBN, and the ethanol aqueous solution obtained in step A2 is 50:2.5:50:100:1000, the centrifugal speed is 5000 rpm, the centrifugal time is 10 minutes, the drying temperature is 75°C, and the drying time is 8 hours.
8. The UV-resistant epoxy copper-clad laminate according to claim 1, characterized in that: The solvent consists of butanone and propylene glycol methyl ether in equal weights.
9. The method for manufacturing a UV-resistant epoxy resin copper-clad laminate according to any one of claims 1 to 8, characterized in that: The following steps are involved: B1. Weigh the components of the resin glue in parts by weight, mix the bisphenol A epoxy resin, flame retardant, curing agent, accelerator, filler, solvent, and stir to obtain a resin glue; B2. The glass fiber cloth is impregnated with the resin solution obtained in step B1 and baked for 5-10 minutes to obtain a prepreg; B3. Stack 8 prepregs obtained in step B2 together to obtain a multilayer prepreg, cover the upper and lower surfaces of the multilayer prepreg with a copper foil respectively, place them in a hot press, and cool to room temperature to obtain a UV-resistant epoxy resin copper-clad laminate.
10. The method for manufacturing a UV-resistant epoxy resin copper-clad laminate according to claim 8, characterized in that: In the step B2, the baking temperature is 150-180° C.; the hot pressing temperature is 200-230° C., the pressure is 5-8 MPa, and the time is 1-3 hours.
Citation Information
Patent Citations
Preparation method for vinyl polymer coated nano-silica microsphere and modified epoxy resin
CN106589464A
Preparation method of coated filler slurry composition, prepreg comprising slurry composition, laminated board and printed circuit board
CN106674602A
Antibacterial 3D printing material for medical products
CN107118502A
Method for preparing copper-clad laminate by using polyphenylene oxide resin composition
CN108263068A
High-elasticity environment-friendly latex paint and preparation method thereof
CN111393941A